Large Eddy Simulation of flow around a Gas Turbine Outlet Guide Vane - Pradhan, Ansuman (My University, 2014)
Engineering flows in the practical world are chaotic and comprise of many different scales of motion due to the influence of ambient noise or disturbances. Such disturbances have a significant impact on the nature of flow close to the boundaries/walls. To simulate such flows near the boundaries correctly constitutes an important aspect of designing and product development processes. In the present thesis flow around a low-pressure turbine outlet guide vane (LPT-OGV) is studied using Large Eddy Simulations (LES). Effort is made to capture the boundary layer transition over the guide vane, which has a crucial impact on the heat transfer characteristics at the vane walls. The results are compared with experimental studies performed on the OGV at the department. Previous simulations based on this experimental study was performed via RANS (Reynolds averaged Navier Stokes) modelling approach. It is the first time that LES is being used. A finite volume method based in-house solver in Fortran, called CALC-LES, is used for performing simulations. The computational grid is created using another inhouse meshing utility, called G3DMESH. The solver of CALC-LES uses a geometric multigrid algorithm to solve the pressure (poisson) equation. In the present thesis, this implementation is studied thoroughly and modifications are made to render it operable for boundary conditions similar to that of the present problem. Two different subgrid scale (SGS) models are used for performing comparative studies – the Smagorinsky-Lilly model and the Germano-Lilly dynamic model. The present simulations fail to capture the transition in the boundary layer over the OGV. The pressure distribution corroborates with the experimental data; but the same cannot be said for the heat transfer at the walls. Mesh independence study showed that the spanwise resolution and domain width of the mesh hardly played any role in transition. Better result from a mesh with finer streamwise resolution in the transition zone indicated that probably a finer streamwise mesh throughout the surface is required for transition prediction. Studying the resolved Reynolds stress components in the boundary layer revealed that the streamwise stress component increased in magnitude significantly, but it doesn’t get distributed into the other components. As a result transition is not observed. Further inspection of the turbulent kinetic energy peak showed that probably the streamwise streaks grow, but either they were not big enough to trigger transiiton or there was no continuous forcing provided by the free-stream turbulence to trigger transition.
Keywords: Energi; Transport; Hållbar utveckling; Strömningsmekanik och akustik; Energy; Transport; Sustainable Development; Fluid Mechanics and Acoustics